Predicting Progression, Recurrence, and Survival in Pancreatic Neuroendocrine Tumors: A Single Center Analysis of 174 Patients - Krogh, Sara; Grønbæk, Henning; Knudsen, Anders Riegels; Kissmeyer-Nielsen, Peter; Hummelshøj, Nynne Emilie; Dam, Gitte (Frontiers in Endocrinology, 2022)
Introduction: The European Neuroendocrine Tumor Society, ENETS, reports variables of prognostic significance in pancreatic neuroendocrine tumors (PNET). However, studies have short follow-up, and the optimal treatment remains controversial. We aimed to determine overall survival (OS), progression free survival (PFS) after conservative treatment and recurrence free survival (RFS) after surgery and further to find predictors of aggressive PNET behavior to support treatment decision. Methods: 174 patients with PNET treated at Aarhus University Hospital from 2011-2021 were included in a retrospective cohort study. Patients were divided into surgically resected (SUR, n=91) and medically or conservatively treated (MED, n=83). Variables were tested in a univariate and multivariate survival analysis. Median follow-up time was 3.4 years in the MED group and 4.5 years in the SUR group. Results: The 5-year OS was 95% and 65% for the SUR and MED groups, respectively. The 5-year RFS in the SUR group was 80% whereas the 5-year PFS in the MED group was 41%. Larger tumor size, Ki67 index, tumor grade, and stage were predictive of shorter OS, RFS and PFS. Further, chromogranin A was a predictor of OS. Larger tumor size was associated with higher stage and grade. Only 1 of 28 patients with stage 1 disease and size ≤2 cm developed progression on a watch and wait strategy during a median follow-up of 36 months. Conclusion: This study supported the ENETS staging and grading system to be useful to predict OS, PFS and RFS in PNET. Further, our data supports that small, localized, low grade PNETS can can be followed with active surveillance.